Preparation method of two-dimensional high-entropy ceramic-based composite aerogel

By adopting two-dimensional sheet self-assembly technology in high-entropy ceramic aerogels, combining graphene aqueous solution for hydrothermal reaction and high-temperature annealing, the mechanical properties of high-entropy ceramic aerogel materials are solved and high strength is achieved and compression resilience under large strains have expanded its application scenarios.

CN119241260AActive Publication Date: 2025-01-03LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411480774.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-03
Estimated Expiration
2044-10-23

Smart Images

  • Figure CN119241260A_ABST
    Figure CN119241260A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of two-dimensional high-entropy ceramic-based composite aerogel, which comprises the following steps: preparing a precursor solution by taking a polyacetylacetone metal complex as a ceramic precursor and an alcoholic solution as a solvent, and synthesizing high-entropy ceramic-based composite hydrogel through a hydrothermal reaction at a specific temperature. The two-dimensional high-entropy ceramic-based composite aerogel is obtained by combining a directional freeze drying process and a high-temperature annealing process. According to the method, a two-dimensional lamella is used as a structural element of the aerogel, and the high-entropy ceramic-based aerogel is constructed from bottom to top through self-assembly of a molecular level, so that the problem of pulverization of one-dimensional fiber aerogel in a pressed process can be effectively solved, and the application scene of the ceramic aerogel is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a two-dimensional high-entropy ceramic-based composite aerogel, and belongs to the technical field of aerogels. Background Art

[0002] High entropy ceramics are multi-component single-phase solid solutions composed of five or more elements in equal or nearly equal atomic ratios. Due to their thermodynamic high entropy effect, structural distortion effect, kinetic hysteresis diffusion effect and "cocktail" effect in performance, they have many outstanding properties and have broad application prospects in thermal protection, catalysis, energy storage, hot pressing and thermoelectricity.

[0003] As an excellent and efficient thermal insulation material, ceramic aerogel has been widely used in various extreme high temperature engineering systems. However, with the continuous development of engineering technology, the requirements for aerogel materials in terms of high temperature resistance, thermal shock resistance, mechanical strength and structural stability are increasing. High entropy ceramics have become a new direction for the development of ceramic aerogel materials due to their excellent thermodynamic stability and chemical uniformity.

[0004] Combining the design concept of high entropy materials with the structural design of aerogels is expected to further improve the overall performance of aerogel materials. This composite material can not only maintain the excellent mechanical and thermal properties of high entropy ceramics, but also take advantage of the light weight and high specific surface area of ​​aerogels to broaden their application prospects in aerospace, energy storage, and environmental protection. With the deepening of research, high entropy ceramic aerogels are expected to play an important role in advanced materials science.

[0005] At present, there are few studies on high-entropy ceramic aerogels. The most commonly used sol-gel method is also used to prepare high-entropy ceramic aerogels. The ceramic aerogels obtained by this method have high porosity and low thermal conductivity, but they do not solve the problem of ceramic brittleness and do not have high compressibility and resilience under large strain. Subsequently, one-dimensional high-entropy ceramic fiber aerogels are constructed by electrospinning, melt spinning or solution blowing processes. One-dimensional fibers are used as structural elements to achieve high compression resilience under large deformation. However, the fiber ceramic aerogels constructed with one-dimensional fibers as structural elements have low strength. At the same time, under long-term strain service conditions, due to the continuous bending and recovery of micro-nano fibers, fiber embrittlement and powdering problems will inevitably occur, resulting in material failure. Summary of the invention

[0006] The purpose of the present invention is to disclose a method for preparing a two-dimensional high-entropy ceramic-based composite aerogel. The method uses two-dimensional sheets as the structural elements of the aerogel, and constructs a high-entropy ceramic-based aerogel from bottom to top through self-assembly at the molecular level, which can effectively improve its own strength. At the same time, it can effectively solve the problems of structural failure caused by embrittlement and powdering of one-dimensional fibers, and broaden the application scenarios of ceramic aerogels.

[0007] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a two-dimensional high entropy ceramic-based composite aerogel comprises the following steps: 1) A high entropy ceramic precursor solution is prepared using polyacetylacetone metal complexes of five elements, namely Zr, Hf, Ti, Lu and Gd, as metal elements and methanol or ethanol as solvent; the high entropy ceramic precursor solution is then added into a graphene aqueous solution and ultrasonically mixed to obtain a hydrothermal precursor solution; wherein the proportion of the high entropy ceramic precursor solution to the graphene solution is 50wt%~200wt%.

[0008] The polyacetylacetonate metal complex comprises polyacetylacetonate titanium, polyacetylacetonate zirconium, polyacetylacetonate hafnium, polyacetylacetonate lutetium and polyacetylacetonate gadolinium, and each polyacetylacetonate metal complex in the metal element is taken in an equimolar amount of the metal element.

[0009] The concentration of the high entropy ceramic precursor solution is 200-400 mg / mL.

[0010] The concentration of the graphene aqueous solution is 2-5 mg / mL.

[0011] 2) The precursor solution obtained in step 1) is transferred into a reactor and subjected to a hydrothermal reaction at 80-120° C. for 6-24 hours to obtain a composite hydrogel. After the reactor is naturally cooled, the reactor is taken out and placed in a 20-50% ethanol solution for dialysis for 20-25 hours. After the dialysis is completed, the reactor is placed on a copper block and liquid nitrogen is used to form ice crystals in the solvent in the composite hydrogel network and completely solidify. The reactor is then taken out and placed in a freeze dryer for drying for 30-40 hours to obtain a composite aerogel precursor.

[0012] 3) placing the composite aerogel precursor in step 2) in an argon-protected tubular furnace, heating to 900-1100°C at a rate of 1-5°C / min for high-temperature annealing, keeping the temperature for 1-2h, and cooling with the furnace to obtain a two-dimensional high-entropy ceramic-based composite aerogel.

[0013] The high temperature annealing is specifically carried out at 1000°C, and the heating process is RT~600°C with a heating rate of 5°C / min, and the heating rate from 600 to 1000°C is 2°C / min.

[0014] The beneficial effects of the present invention are as follows: The present invention prepares ceramic aerogel on a two-dimensional scale for the first time, and the amount of each element substance in the ceramic phase is nearly equal in molar ratio, and each element is evenly distributed.

[0015] The present invention uses polyacetylacetone metal complex as a ceramic precursor, which can be well combined with graphene sheets through chemical bonding during a hydrothermal reaction, and obtains an oxide high-entropy ceramic-based composite aerogel with a single-phase defect fluorite structure after high-temperature annealing.

[0016] The present invention can carry out directional structural design on the two-dimensional composite aerogel, thereby improving the mechanical stability of the aerogel.

[0017] The invention does not require complicated heat treatment and has a simple preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The present invention provides a preparation route for the high entropy ceramic-based composite aerogel.

[0019] Figure 2 This is a SEM image of the high entropy ceramic-based composite aerogel prepared in Example 1 of the present invention parallel to the growth direction of ice crystals.

[0020] Figure 3 This is a SEM image of the high entropy ceramic-based composite aerogel prepared in Example 1 of the present invention, perpendicular to the growth direction of ice crystals.

[0021] Figure 4 XRD patterns of high entropy ceramic-based composite aerogels prepared in Examples 1-3 of the present invention.

[0022] Figure 5 This is a mechanical property curve of the high entropy ceramic-based composite aerogel prepared in Example 1 of the present invention, and the attached small figure is a local enlarged view under 0-70% strain.

[0023] Figure 6 This is the mechanical property curve of the high entropy ceramic-based composite aerogel prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0024] The present invention is further explained below with reference to specific embodiments.

[0025] See also Figure 1 The organic precursors of Zr, Hf, Ti, Lu and Gd used in each embodiment can be synthesized according to the following steps: (1) Hafnium oxychloride octahydrate, zirconium oxychloride octahydrate, lutetium chloride hexahydrate, and gadolinium chloride hexahydrate are dissolved in anhydrous methanol in an equal molar ratio of metal elements. After complete dissolution, acetylacetone is added. After stirring for 1 hour, triethylamine is added dropwise, wherein the molar ratio of metal element: acetylacetone: triethylamine is 1:1:3. After the addition is completed, stirring is continued for 2 hours to obtain a yellow clear solution; (2) Pour the yellow solution obtained in step (1) into a rotary evaporator and distill under reduced pressure at 50° C. to obtain a dry powder of a mixture of triethylamine hydrochloride and polyacetylacetone metal complex, and then dissolve the powder in an appropriate amount of acetone and let it stand for 48 hours; (3) removing the insoluble triethylamine hydrochloride in step (2) by centrifugation to obtain an acetone solution of the polyacetylacetone metal complex, pouring the acetone solution into a rotary evaporator and performing vacuum distillation to dryness at a vacuum distillation temperature of 40° C. to obtain a quaternary metal polyacetylacetone complex precursor powder; (4) For the synthesis of titanium polyacetylacetonate, see Chinese patent document CN104961763A.

[0026] (5) Poly(acetylacetonate) titanium and the quaternary precursor powder obtained in step (3) are dissolved in methanol in an equimolar ratio of the metal elements to prepare a high entropy ceramic precursor solution with a concentration of 200 mg / ml.

[0027] Example 1 The high entropy ceramic precursor solution was added to a 3 mg / ml graphene aqueous solution at a ratio of 50 wt%, and ultrasonic dispersion was performed for 20 min to make it evenly mixed. Then, the mixture was shaken to remove bubbles, and the mixture was placed in a polytetrafluoroethylene-lined reactor and subjected to hydrothermal reaction at 120 °C in a forced air drying oven for 6 h. After the reactor was completely cooled, it was opened to obtain GO-PHEC. 0.5 Composite hydrogel; the hydrogel was then placed in a 20% ethanol solution for 24 h, and after the dialysis was completed, it was placed on a copper block and liquid nitrogen was used to make the solvent in the hydrogel network form ice crystals and completely solidify, and then removed and placed in a freeze dryer for 40 h to obtain GO-PHEC 0.5 Composite aerogel precursors.

[0028] Aerogel structures constructed by directional freezing Figure 2 , Figure 3 shown. Figure 2 This is a SEM image parallel to the growth direction of the ice crystals. In this direction, the high-entropy ceramic-based composite sheets are arranged in an orderly manner along the growth direction of the ice crystals. Figure 3 This is a SEM image perpendicular to the growth direction of ice crystals. In this direction, the high-entropy ceramic-based composite sheets are randomly arranged, which is consistent with the design.

[0029] The composite aerogel precursor was placed in an argon-protected tubular furnace and annealed at 1000 °C. The heat treatment process was 5 °C / min from RT to 600 °C and 2 °C / min from 600 to 1000 °C. After cooling in the furnace, the two-dimensional high entropy ceramic matrix (GO-HEC) was obtained. 0.5 ) composite aerogel.

[0030] Example 2 The high entropy ceramic precursor solution was absorbed at a ratio of 100wt% and added to a 3mg / ml graphene aqueous solution. The mixture was ultrasonically dispersed for 20 min to make it evenly mixed, and then the bubbles were removed by shaking. The mixture was placed in a polytetrafluoroethylene-lined reactor and subjected to hydrothermal reaction at 120°C in a blast drying oven for 6 h. After the reactor was completely cooled, it was opened to obtain a GO-PHEC1 composite hydrogel. The hydrogel was then dialyzed in a 20% ethanol solution for 24 h. After the dialysis was completed, the hydrogel was placed on a copper block and liquid nitrogen was used to form ice crystals in the solvent in the hydrogel network and completely solidified. The mixture was then removed and placed in a freeze dryer for 40 h to obtain a GO-PHEC1 composite aerogel precursor.

[0031] The composite aerogel precursor was placed in an argon protected tubular furnace and annealed at 1000 °C. The heat treatment process was 5 °C / min from RT to 600 °C and 2 °C / min from 600 to 1000 °C. After being taken out, a two-dimensional GO-HEC1 composite aerogel was obtained.

[0032] Example 3 The high entropy ceramic precursor solution was added to the 3mg / ml graphene aqueous solution at a ratio of 150wt%, and ultrasonic dispersion was performed for 20 min to make it evenly mixed. Then, the mixture was shaken to remove bubbles, and the mixture was placed in a polytetrafluoroethylene-lined reactor and subjected to hydrothermal reaction at 120°C in a forced air drying oven for 6 h. After the reactor was completely cooled, it was opened to obtain GO-PHEC. 1.5 Composite hydrogel; the hydrogel was then placed in a 20% ethanol solution for 24 h, and after the dialysis was completed, it was placed on a copper block and liquid nitrogen was used to make the solvent in the hydrogel network form ice crystals and completely solidify, and then removed and placed in a freeze dryer for 40 h to obtain GO-PHEC 1.5 Composite aerogel precursors.

[0033] The composite aerogel precursor was placed in an argon-protected tubular furnace and annealed at 1000 °C. The heat treatment process was 5 °C / min from RT to 600 °C and 2 °C / min from 600 to 1000 °C. After taking it out, the two-dimensional GO-HEC was obtained. 1.5 Composite aerogel.

[0034] Example 4 The high entropy ceramic precursor solution was added to the 3mg / ml graphene aqueous solution at a ratio of 200wt%, and ultrasonic dispersion was performed for 20 min to make it evenly mixed. Then, the mixture was shaken to remove bubbles, and the mixture was placed in a polytetrafluoroethylene-lined reactor and subjected to hydrothermal reaction at 120°C in a blast drying oven for 6 h. After the reactor was completely cooled, it was opened to obtain GO-PHEC. 2.0Composite hydrogel; the hydrogel was then placed in a 20% ethanol solution for 24 h, and after the dialysis was completed, it was placed on a copper block and liquid nitrogen was used to make the solvent in the hydrogel network form ice crystals and completely solidify, and then removed and placed in a freeze dryer for 40 h to obtain GO-PHEC 2.0 Composite aerogel precursors.

[0035] The composite aerogel precursor was placed in an argon-protected tubular furnace and annealed at 1000 °C. The heat treatment process was 5 °C / min from RT to 600 °C and 2 °C / min from 600 to 1000 °C. After taking it out, the two-dimensional GO-HEC was obtained. 2.0 Composite aerogel.

[0036] The product structure characterization and performance evaluation are as follows: The XRD patterns of the composite aerogels prepared in the above examples 1-3 are as follows: Figure 4 As shown. Figure 4 It can be seen that high entropy ceramic-based aerogel has been successfully synthesized.

[0037] Then, GO-HEC prepared in Example 2 was taken 0.5 The mechanical properties of the composite aerogel were evaluated. According to the size data of the aerogel, the compression test was carried out after the gauge length was determined. The compression curve was obtained under the conditions of loading speed of 5 mm / min and strain of 30%, 60%, and 90%. Figure 5 As shown. Figure 5 It can be seen that the high-entropy ceramic-based composite aerogel still has excellent compression-rebound properties under a large strain of 90%.

[0038] Comparative Example 1 The same high entropy ceramic precursor solution was used, except that the hydrothermal solution was only a graphene aqueous solution, and the other steps were the same as in Example 2 to obtain a graphene hydrogel. The high entropy ceramic precursor was combined with the graphene hydrogel using a vacuum impregnation process, and the heat treatment process remained unchanged. The mechanical properties of the obtained GO-HEC composite aerogel were as follows: Figure 6 It can be seen that under the same strain, the mechanical properties of the high entropy ceramic-based composite aerogel obtained by in-situ hydrothermal modification are much better than those of the high entropy ceramic-based aerogel obtained by the impregnation process.

Claims

1. A method for preparing a two-dimensional high entropy ceramic-based composite aerogel, characterized in that: The following steps are involved: 1) Using polyacetylacetone metal complexes of five elements, Zr, Hf, Ti, Lu, and Gd, as metal elements and methanol or ethanol as solvent, a high entropy ceramic precursor solution is prepared; then the high entropy ceramic precursor solution is added to the graphene aqueous solution and ultrasonically mixed to obtain a hydrothermal precursor solution; wherein the proportion of the high entropy ceramic precursor solution to the graphene solution is 50wt%~200wt%; 2) The precursor solution obtained in step 1) is transferred into a reactor and subjected to a hydrothermal reaction at 80-120° C. for 6-24 hours to obtain a composite hydrogel. After the reactor is cooled naturally, the precursor is taken out and placed in a 20-50% ethanol solution for dialysis for 20-25 hours. After the dialysis is completed, the precursor is placed on a copper block and liquid nitrogen is used to make the solvent in the composite hydrogel network form ice crystals and completely solidify. The precursor is then taken out and placed in a freeze dryer for drying for 30-40 hours to obtain a composite aerogel precursor. 3) placing the composite aerogel precursor in step 2) in an argon-protected tubular furnace, heating to 900-1100°C at a rate of 1-5°C / min for high-temperature annealing, keeping the temperature for 1-2h, and cooling with the furnace to obtain a two-dimensional high-entropy ceramic-based composite aerogel.

2. A method for preparing a two-dimensional high entropy ceramic-based composite aerogel as claimed in claim 1, characterized in that: In step 1), the polyacetylacetonate metal complex comprises polyacetylacetonate titanium, polyacetylacetonate zirconium, polyacetylacetonate hafnium, polyacetylacetonate lutetium and polyacetylacetonate gadolinium, and each polyacetylacetonate metal complex in the metal element is used in an equimolar amount of the metal element.

3. The method for preparing a two-dimensional high entropy ceramic-based composite aerogel according to claim 1, characterized in that: In step 1), the concentration of the high entropy ceramic precursor solution is 200-400 mg / mL.

4. The method for preparing a two-dimensional high entropy ceramic-based composite aerogel according to claim 1, characterized in that: In step 1), the concentration of the graphene aqueous solution is 2-5 mg / mL.

5. The method for preparing a two-dimensional high entropy ceramic-based composite aerogel according to claim 1, characterized in that: In step 3), high temperature annealing is specifically performed at 1000°C, the heating process is RT~600°C with a heating rate of 5°C / min, 600~1000°C with a heating rate of 2°C / min, and 1000°C is kept for 2h.

Citation Information

Patent Citations

  • Method for preparing hyperelastic silicon oxide nano ceramic aerogel based on graphene as template

    CN112794705A

  • Preparation method of oxide high-entropy ceramic fiber

    CN113307632A

  • Preparation method of graphene oxide composite aerogel with alignment channels and thermal response

    CN113398895A

  • Fluorite-structure high-entropy ceramic aerogel powder with low thermal conductivity and preparation method of fluorite-structure high-entropy ceramic aerogel powder

    CN113401939A

  • Mxene / metal composite aerogel, preparation method therefor and use thereof, and thermal interface material containing same

    WO2021056851A1

Cited By

  • Yttrium-zirconium ceramic fiber aerogel with grain boundary segregation phenomenon and high infrared reflectivity

    CN121494552A